The methanol and CO electro-oxidation onto Ptpc/Co/Pt metallic multilayer nanostructured electrodes: An experimental and theoretical approach. (1st August 2018) - Silva, C.D.; Morais, L.H.; Gonçalves, R.; Matos, R.; Souza, G.L.C.; Freitas, R.G.; Pereira, E.C.
Abstract: We developed Ptpc /Co/Pt nanostructured metallic multilayers (MM) electrodes for methanol and carbon monoxide electro-oxidation. This material uses as an intermediate layer a non-noble metal (cobalt), which is a low cost material. Cyclic voltammetry was used to characterize the electrode electrochemical behaviour for methanol and carbon monoxide. In addition, electrochemical impedance spectroscopy (EIS) was used to study the methanol oxidation on these multilayers. An increase in the peak current density of about 35% for Ptpc /Co10 /Pt5 nanostructured metallic multilayer compared to Ptpc electrode was observed for methanol oxidation reaction (MOR). Carbon monoxide electro-oxidation showed large current density for all multilayers electrodes and the onset potentials for this reaction was displaced toward more negative potentials, which indicates weaker adsorption energy for CO over the surface of the materials compared to Ptpc . EIS data indicated a lower charge transfer resistance (Rct ) for Ptpc /Co10 /Pt5 MM nanostructured during the methanol electro-oxidation, that indicates higher electrocatalytic activity for this electrode compared to Ptpc . Computational modelling results indicate that the presence of a Co-underlayer for Pt/Co/Pt (111) nanostructured system decrease the center of d -band and, consequently, increase the catalytic activity compared to Pt (111) system.